Autophagy in health and disease: From molecular mechanisms to therapeutic target. Issue 3 (10th July 2022) - Lu, Guang; Wang, Yu; Shi, Yin; Zhang, Zhe; Huang, Canhua; He, Weifeng; Wang, Chuang; Shen, Han‐Ming
Abstract: Macroautophagy/autophagy is an evolutionally conserved catabolic process in which cytosolic contents, such as aggregated proteins, dysfunctional organelle, or invading pathogens, are sequestered by the double‐membrane structure termed autophagosome and delivered to lysosome for degradation. Over the past two decades, autophagy has been extensively studied, from the molecular mechanisms, biological functions, implications in various human diseases, to development of autophagy‐related therapeutics. This review will focus on the latest development of autophagy research, covering molecular mechanisms in control of autophagosome biogenesis and autophagosome–lysosome fusion, and the upstream regulatory pathways including the AMPK and MTORC1 pathways. We will also provide a systematic discussion on the implication of autophagy in various human diseases, including cancer, neurodegenerative disorders (Alzheimer disease, Parkinson disease, Huntington's disease, and Amyotrophic lateral sclerosis), metabolic diseases (obesity and diabetes), viral infection especially SARS‐Cov‐2 and COVID‐19, cardiovascular diseases (cardiac ischemia/reperfusion and cardiomyopathy), and aging. Finally, we will also summarize the development of pharmacological agents that have therapeutic potential for clinical applications via targeting the autophagy pathway. It is believed that decades of hard work on autophagy research is eventually to bring real and tangible benefits for improvement of human health and control of human diseases. Abstract : Macroautophagy/autophagy is an evolutionally conserved catabolic process induced under various stress conditions to maintain intracellular homeostasis. Dysregulation of autophagy is closely associated with various human diseases. This review will focus on the molecular mechanisms in control of autophagy, the implication of autophagy in various human diseases, and the development of pharmacological agents that target autophagy.